Parental Involvement In Diverse Family Structures: a Qualitative Analysis of its Role in Elementary Students Learning Outcomes - Muhammad Feri Dimyati; Siti Faizah; Riska Pristiani (Sistem-Among : Jurnal Pendidikan Sekolah Dasar, 2026)
Parental involvement plays a crucial role in supporting children's academic success. Previous studies have mostly focus on quantitative relation and have not deeply explored the form of parental involvement in specific elementary school contexts. This study aims to describe the forms of parental involvement and its relationship with students’ learning outcomes at SDN Kromengan 1, Malang Regency. The research uses a qualitative approach involving six students who met the criteria along with their parents to allow in-depth exploration. Data were collected through observation, interviews, and documentation. The findings reveal that parental involvement is strongly associated with students’ learning outcomes, particularly in the cognitive domain (academic achievement) and the affective domain (motivation and classroom engagement), while differences in psychomotor aspects were less prominently observed. On the other hand, students who receive less involvement are more likely to have lower academic results. Parental involvement can include involvement in learning activities, effective communication, as well as moral and material support. In conclusion, This study indicates that parental involvement is closely associated with students’ academic achievement in the observed context. This study contributes by providing a contextual understanding of how different forms of parental attention shape students’ learning outcomes at the elementary level.